A comparative account of the microbial biomass-N and N-mineralization of soils under natural forest, grassland and crop field from dry tropical region, India - Jay S. Singh; D.P. Singh; A.K. Kashyap (Plant, Soil and Environment, 2009)
This study investigated microbial biomass-N (MB-N) and N-mineralization in soils of four different vegetation systems including forest (sal), mixed forest, savanna and cropland ecosystems in the Vindhyan region, India. A change was noted in the above region due to physiographic differences and anthropogenic disturbances. Annually the soil moisture (SM) content across the different study sites ranged from 7.5 to 24.3% being maximum in forest sites compared to savanna and cropland sites. The NH4+-N, NO -3 -N and MB-N concentrations varied from 4.3 to 10.2 μg/g, 1.1 to 5.8 μg/g and 21.3 to 90.2 μg/g dry soil, respectively, with minimum values in the wet and maximum values in the dry season. The trend of seasonal variation in net N-mineralization was similar to that of moisture content but counter to the concentrations of inorganic-N and MB-N. The net N-mineralization rates at different investigated sites ranged from 4.5 to 37.6 μg/g month. Cultivation reduced the N-mineralization and MB-N by 58.5% and 63.5%, respectively. Experiments showed that the percentage contribution of MB-N to total-N was 8.01 to 19.15%. MB-N was positively correlated with the inorganic-N (n = 180,r.80,P < 0.001) but negatively with soil moisture (n = 180, r = 0.79, P < 0.001) and net N-mineralization rates (n = 180, r = 0.92, P < 0.0001). The higher N-mineralization and MB-N in the soil of forest ecosystem was reported compared to savanna and cropland and the order of soil MB-N levels and net N-mineralization followed the sequence: forest (sal) > mixed forest > savanna > cropland.